Plasma Treatment of Carbon Nanofibers Using an Anode Layer Ion Source for High-Performance Electrochemical Capacitors. (21st November 2014) - Lee, Yu-Jin; Kim, Do-Geun; Ahn, Hyo-Jin
Abstract : We synthesized carbon nanofibers(CNFs) by electrospinning and then activated their surface states via plasma treatment with an anode layer ion source. We studied the effects of various treatment times—0, 400, 800, and 1200 seconds—in order to identify the optimum conditions for plasma treatment. We investigated the morphological and structural properties, and the chemical composition of the CNFs using scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, Fourier transform infrared spectroscopy, and X-ray photoelectron spectroscopy. The activated CNFs—plasma-treated for 1200s—exhibited excellent capacitance(∼173.25 F/g at 5 mV/s), superb cycling stability(∼92.59%), and the highest energy density(∼6.81 Wh/kg) among the different samples produced.